Pengaruh Strategi Pembelajaran Inkuiri Terhadap Hasil Belajar Peserta Didik Dalam Pembelajran PAI - Aini Mardiah; Khairuna Fitri Lubis; Gusmaneli Gusmaneli (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The purpose of this writing is to discuss inquiry learning strategies. The inquiry learning strategy states that teachers are not the only learning source, there are many other learning sources that can support successful learning. The teacher is only a facilitator, a guide who always directs students in learning. Students are designed as discoverers or seekers of knowledge, a teacher's job is to manage students so that they gain knowledge and become meaningful. Because with meaning the knowledge will enter their knowledge, so that it will always be remembered by students. The student does everything the teacher only prepares, because the student does the learning will be a meaningful experience for the student.